Efektivitas Belajar Daring dalam Meningkatkan Hasil Belajar Siswa SMA di Jakarta Selatan - Nurlaela Nurlaela (SAP (Susunan Artikel Pendidikan), 2022)
The COVID-19 pandemic period makes students have to study at home but there are obstacles during study at home, these obstacles include learning equipment such as laptops, or internet networks, as well as the role of parents. Therefore, it carried out a research aimed at finding out how much effectiveness there is in applying bold learning to high school children's learning outcomes and to find out what methods are appropriate for bold learning in 2020. The method in this research is correlational to test the truth of the hypothesis by using regression simple linear analysis. Based on the results, it can be said that continuous online learning for students in the Tanjung Barat area, South Jakarta is less effective, this is due to the constraints experienced by students and parents in online learning both in terms of material that is less than half of the material that students can absorb and the ability of teachers, students and even parents in using the internet which is still low.